Ion Chromatographic Method for the Simultaneous Determination of Anions and Cations in Firecrackers and Matches Samples as Known Potential Explosives - Lee Wah Lim; Muhammad Amin (UNIVERSITAS SEBELAS MARET (UNS), 2019)
A reference ion chromatography method based on column switching has been presented for the simultaneous determining anions (Cl−, ClO3−, NO2−, SO42−, and NO3−) and/or cations (NH4+, Na+, K+, Ca2+, and Mg2+) using one pump, one type of mobile phase, and one detector. The reference method performed anion-exchange column and cation-exchange column and arranged serially via one 10-port valve. The determination of either anions or cations in one determination system could be made by switching the valve. When the use of 1.25 mM trimellitic acid as a mobile phase and the instrument was operated at a flow rate of 0.6 mL/min, five anions and five cations were determined on the anion-exchange column and the cation-exchange column, respectively. All anions target could be determined completely within 55 minutes, whereas the cations target could be determined within 35 minutes. The calculation of limit of detection using S/N=3 was 3.85 − 14.10 µM for anions and 2.95 − 10.58 µM for cations. The relative standard deviations of all ions were less than 3.82%, 3.29%, and 3.21% for retention time, peak area, and peak height, respectively. The reference method was then applied for the simultaneous determining anions and/or cations contained in firecrackers and matches samples as known potentially explosives.